Cash-Flow Tax - Schutte, Christian; Shome, Parthasarathi (Washington, D.C. : International Monetary Fund, 1993)
The cash-flow tax has been proposed as an alternative to corporate income tax on grounds of clarity and simplicity in defining the tax base in the face of widespread departures from the comprehensive income tax in actual practice. Variants of the tax, with their advantages and disadvantages, demonstrate that it would require careful design. Simplicity is not an obvious property because of expectable administration problems related to tax avoidance and evasion through transfer pricing; to inflation adjustments; and to incompatibility with existing international tax regimes. Thus, the tax remains theoretically attractive but difficult to implement by a single--especially developing--country.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet